Filsafat Pendidikan Seodjatmoko: Pendidikan sebagai Pencarian Identitas Diri - Dinda Muslimah Ardiyenti; Radea Yuli A Hambali (Gunung Djati Conference Series, 2023)
Educational philosophy is a branch of science that studies the principles and basic goals of education. Seodjatmoko emphasized that education must help students find their identity, so that they can develop their potential and become superior individuals. The research method that can be used is descriptive qualitative method. Education as a search for self-identity is a holistic process, which does not only focus on academic aspects, but also includes individual emotional, social and spiritual aspects. Seodjatmoko's philosophy of education emphasizes that education is not just a process of transferring knowledge, but also a process of individual transformation. Educational philosophy is a branch of philosophy that studies the nature, goals, and ways of achieving educational goals.